Virtual Assistant For Health Care Services - et. al., G. Preethi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Patients have become responsive to the importance of taking secure management and managing access to their medical information, thereby increasing the adoption of non-public health record systems. During any circumstances like the covid-19 pandemic, people adapted themselves towards technological improvements. We have seen many works were completed without human physical involvement. When we consider the healthcare domain the virtual platforms made were not used. One of the main reasons is there is no unique platform for the virtualization of the healthcare domain. As a result, the stability of the virtual health care services is lost. So here we came up with the idea of ‘Virtual Assistant for Health Care Services. The virtual assistant for health care services key aim is to incorporate several hospitals. This project aims to provide patients with consistent and reliable medical solutions from seasoned doctors across the internet. This initiative also removes the need for redundant medical records. The patient will be able to save time and money as a result of this initiative. Telemedicine allows health care professionals to evaluate, diagnose and treat patients at a distance using telecommunications technology. It assists in the elimination of geographical barriers and can increase access to medical services that are not always accessible in remote rural areas. This initiative aims to bring healthcare services to people in remote areas that have access to the internet. Medical records generated in one hospital can be used in any other hospital that is linked to this site. It can monitor testing results as well as patient health information.